EVALUASI EFEKTIVITAS TATA KELOLA SAMPAH DI TEMPAT PENGOLAHAN SAMPAH TERPADU (TPST) TOSS CENTER GEMA SANTI KABUPATEN KLUNGKUNG - Bharata Wicaksana, A. A. Gede Agung; Diara, I Wayan; Adnyana, Ida Bagus Windia (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024), 2024)
Despite various national and regional waste management efforts, the outcomes remain suboptimal, particularly in facilities like TPST and TPS3R. This study evaluates the effectiveness of waste management at TPST TOSS Center Gema Santi in meeting the 2025 JAKSTRADA targets, focusing on waste reduction and handling, cost-benefit analysis (CBA), and human resource (HR) competencies. From January 2023 to April 2024, the facility achieved a combined waste reduction and handling rate of only 15.7%, with a ZWI score of 0.11 in 2023 and 0.06 from January to April 2024. The CBA for the same period showed a BCR of 0.23 and a net value of -Rp1,293,846,839. HR competency was found to be strong in terms of knowledge, attitude, and practice. In conclusion, TPST TOSS Center Gema Santi has not met the 2025 JAKSTRADA targets of 30% waste reduction and 70% waste handling, primarily due to operational inefficiencies where costs outweigh benefits. However, the strong HR competencies suggest potential for improvement. Key recommendations include strengthening waste management policies, promoting waste sorting at the source, fostering collaboration with stakeholders, adopting automated technologies for operations, and providing continuous training to enhance HR capacity. Keywords: TPST; Evaluation; Waste management effectiveness; HR Competency